(untitled) (GEON Journal (Management, Organizations and Business), 2018)
This project proposes the integration of technological and didactic tools in the teaching of experimental and exact sciences under the approach and principles of the Substitution-Increase-Modification-Redefinition model (SAMR model). It is important to highlight that the SAMR model proposes a process that allows improving the quality of teaching and learning based on the integration of technological tools and teaching strategies. The integration of this model makes it clear that ICT can transform traditional learning environments into four progressive levels of impact (Substitution, Increase, Modification and Redefinition, hence the name of the SAMR model). However, it is important to keep in mind that not all technological tools will achieve all four levels in an inertial manner. In this sense, the teacher must select and integrate the tools taking into account the potential impact that in their opinion these can reach. In this project, the use of simulators as substitute elements of preexisting methodologies for the learning of essential topics in the area of exact and experimental sciences was prioritized. These simulators achieved different levels of impact when integrated with specific didactic tools. Under this approach, technological tools were applied in such a way that they could be conceived as a substitution, increase, modification or redefinition of other traditional tools, but with functional improvements. The incorporation of this model, at the end of the day, allowed students to enter into a dynamic of exploring, describing, explaining, evaluating and / or transforming, developing in them a critical, analytical and divergent thinking.